The Obligation of Notary as a Reporter in Efforts to Prevent and Eradicate Money Laundering Crime - Erwin Kunta Tejakusuma; Dwi Endah Nurhayati; Samuel Saut Martua Samosir (Jurnal Ilmu Kenotariatan, 2024)
Money laundering is a structured and diverse crime, the implementation of which can utilize financial institutions and institutions outside the financial system. In Government Regulation No. 43/2015 on Reporting Parties in the Prevention and Eradication of ML, it is stated that notary is one of the reporting parties. However, this obligation to report conflicts with the obligation to keep the contents of the deed and all information regarding the deed confidential as stipulated in the Notary Position Law. Notaries in carrying out their duties are bound by an oath of office that they must uphold. One of the notary oaths is regarding notary confidentiality as written in Article 4 Paragraph (2) of Law Number 30 Year 2004. In addition, notaries in carrying out their positions, based on Article 16 of UUJN Paragraph (1) letter f, notaries are obliged to "keep confidential everything regarding the deed they make and all information obtained for the making of the deed in accordance with their oath / pledge of office, unless the law determines otherwise". The clash of norms between private law and public law certainly requires legal protection in carrying out their positions. The legal protection applied is related to the guarantee of the rights and obligations of notaries, both regarding their obligations as reporting parties in efforts to prevent and eradicate money laundering crimes and notary obligations in the realm of private law. This legal protection is intended so that notaries can be free from claims or lawsuits in carrying out their obligations as reporting parties in efforts to prevent and eradicate money laundering crimes. KEYWORDS : Notary, Obligations of the Reporting Party, Legal Protection.